A Simple Macrofiscal Model for Policy Analysis : An Application to Cambodia - Baksa, Daniel; Bulir, Ales.; Heng, Dyna. (Washington, D.C. : International Monetary Fund, 2020)
The paper describes a semistructural macrofiscal approach to simulating and forecasting macroeconomic policies. Our canonical model is adapted to Cambodia and we demonstrate its application with an illustrative scenario of macroeconomic effects of the Covid-19 pandemic. Complemented with near-term forecasting tools and expert judgment, the dynamics of the model helps to inform policymakers about medium-term transmission channels and thus guide policy advice.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet